Pengaruh Metode Pijat Tui Na Terhadap Penambahan Berat Badan pada Balita Usia 1-5 Tahun dengan Masalah Berat Badan dan Picky Eater: Effect of the Tui Na Massage Method on Weight Gain in Toddlers Aged 1-5 Years with Weight Problems and Picky Eaters - Kusuma Intan Setianing Fifit; Luvi Dian Afriyani (Journal of Holistics and Health Sciences (JHHS), 2023)
Growth problems that often arise in toddlers are nutritional problems, many factors influence the incidence of malnutrition including hereditary factors and environmental factors (Saidah, 2020). Based on a field survey, data were obtained at PMB Noor Naini Semarang City in August-September 2022 with the main problem being that 2 toddlers were found to be undernourished or under the red line and 4 other toddlers had difficulty eating. Stimulation or stimulation that is good for children can be given for maximum growth, one of which is tui na massage. The purpose of this study was to determine the effect of the Tui Na massage method on increasing body weight in toddlers aged 1-5 years at PMB Noor Naini Semarang City in 2022. The type of research used was pre-experimental designs with one group pretest-posttest design. The number of samples in this study were 13 toddlers with the sample criteria for toddlers aged 1-5 who experienced malnutrition, inappropriate body weight and experienced eating problems. The sampling technique uses purposive sampling. Data analysis used independent paired sample t test. The results of statistical tests using paired t test with a value of p = 0.000. Because the calculation results show that p <0.05 then Ho is rejected, and Ha is accepted. In conclusion, there is an effect of baby massage on increasing the weight of toddlers aged 1-5 years at PMB Noor Naini Semarang City in 2022 ABSTRAK Permasalahan pertumbuhan yang sering muncul pada balita adalah masalah gizi, banyak faktor yang mempengaruhi kejadian gizi kurang antara lain faktor herediter dan faktor lingkungan (Saidah H, 2020). Berdasarkan survey lapangan didapatkan data di PMB Noor Naini Kota Semarang pada bulan Agustus-September tahun 2022 dengan  permasalahan utama yaitu 2 balita ditemukan dengan gizi kurang atau berat badan dibawah garis merah serta 4 balita lainnya mengalami kesulitan makan. Stimulasi atau rangsangan untuk anak dapat diberikan untuk pertumbuhannya secara maksimal salah satunya pijat tui na. Tujuan penelitian ini adalah untuk mengetahui pengaruh metode pijat Tui Na terhadap penambahan berat badan pada balita usia    1 – 5 tahun di PMB Noor Naini Kota Semarang Tahun 2022. Jenis penelitian yang digunakan adalah pre experimental designs dengan rancangan one group pretest-posttest. Jumlah sampel dalam penelitian ini sebanyak 13 balita dengan kriteria sampel balita usia 1-5 yang mengalami masalah berat badan & masalah makan. Teknik sampling menggunakan Purposive sampling. Analisis data menggunakan uji  paired sample t test dengan nilai p = 0,000. Oleh karena hasil perhitungan menunjukkan bahwa p < 0,05 maka Ho ditolak, dan Ha diterima. Kesimpulannya terdapat pengaruh pijat tui na terhadap penambahan berat badan balita usia 1-5 tahun di PMB Noor Naini Kota Semarang Tahun 2022